The Effectiveness of Powerpoint Multimedia in Learning Motivation and Cognitive Science Learning Outcomes of Elementary School Students - Serly Serly; Rusli Rusli; Rifat Shafwatul Anam (PT ARRUS Intelektual Indonesia, 2023)
This study focuses to the analyze effectiveness of using multimedia powerpoint in learning science for elementary school students. The purposes of this study are to knowing the effectiveness of Multimedia Powerpoint as a learning media on the motivation and science learning outcomes of fifth grade elementary school students. With quantitative approach and Pre-Experimental Design One Group Pretest-Posttest Design model. The population in this study were all fifth grade students at SD Gugus Salubarani for the academic year 2022/2023 with a total of 93 students. To get sample used cluster random sampling type with which was carried out through class randomization and obtained class V SDN 292 Inpres Karangan as the sample. Based on the results of statistical data analysis using a one sample t test with a 95% confidence level, the t value is 4.043 where the value is t¬table = 1.72074 (4.043 > 1.72074) so it can be concluded that H1 is accepted, the student's motivation is as expected, which is more than 36 or in general the motivation to learn science. The fifth grade elementary school students in the Salubarani group are in the medium category after learning using powerpoint media. In addition, based on the results of the calculation obtained a normalized gain value = 0.43972 which states that the increase in learning motivation of grade V elementary school students in the Salubarani cluster is in the medium category.Based on the results of hypothesis testing with a test value of 75 and a 95% confidence level, the value of tcount = 3.699, which is more than the value of t¬table = 1.72074 (3.699>1.72074) this shows that the average science learning outcomes of Grade V elementary school students the salubarani group is more than or equal to 75 after being taught using Multimedia Powerpoint.